Growth of trees in secondary forest - Yong, P. L.; Ong, Kian Huat; King, Jie Hung (2012)
Secondary forest is a forest regenerates in through natural processing after human disturbance. Objective of this study was to investigate growth rate of tree species in a secondary forest. This study was carried out in 10 established plots of 50 × 20 m at Nurwana Forest, a 16-year-old logged-over forest in Universiti Putra Malaysia Bintulu Sarawak Campus. In this study, tree species with 10 cm diameter breast height and above were selected. Majority of tree (78%) were found in smaller diameter class with only 0.8% having diameter more than 55 cm. The diameter growth rate in Nirwana Forest was better as compared to other reported results either in primary forest or secondary forest.